Hubungan antara Kekuatan Karakter dengan Kebahagiaan pada Remaja di SMA Aziziah Palembang - Afrida Assadilla Henisa; Zuhdiyah Zuhdiyah; Fajar Tri Utami (Indonesian Journal of Behavioral Studies, 2021)
This Research discusses the relationship between character strength and happiness in adolescents at Aziziah High School Palembang. This study aims to determine whether there is a relationship between character strength and happiness in adolescents at Aziziah High School Palembang. By using quantitative research. The sample used in the study amounted to 150 students. The data analysis method used is product moment analysis. Based on the results of the research that has been carried out, it can be concluded that there is a significant relationship between character strength and happiness in adolescents, based on the results of this study it proves that there is an influence between character strength and happiness in adolescents at Aziziah High School Palembang as evidenced by the correlation coefficient value which shows the r = 0.561 with a value of Sig. p = 0.000 < 0.05, so from these results it can be seen that there is a relationship, meaning that the higher the strength of the character, the higher the happiness of the students.